Spatiotemporal Detection of Dust Seasonal Extremes in Kurdistan Province from MACC and MODIS - kaveh mohammadpour; MOhammad Saligheh; Tayeb Raziei; Ali Darvishi Bloorani (تحقیقات کاربردی علوم جغرافیایی)
Mineral Dust, the most important type of aerosol, has a significant direct and indirect role in weather and climate. In this case, it intend to investigate the capability and capability of MACC model validated by MODIS for detection of dust episodes in the Kurdistan province during 2003-2012. To achieve that, we analysis satellite and model data using Man-Kendall trend and statistical tests. The results of the temporal distribution indicated that the mean Aerosol Optical depth (AOD) in 2008 was 0.36 and its lowest was 29.04 for 2004. In addition, average AOD in menthioned year was 0.036, 0.335, 0.385, 0.377 and 0.3368 for the cities of Sanandaj, Saqez, Ghorveh, Kamyaran, Marivan, respectively. The spatial distribution of AOD average in different seasons showed that winter and autumn had the lowest amount and spring, and summer season had the highest AOD. AOD's monthly spatial distribution showed that high dust belonging to April-August period to covers completely interested area.The results of the Man-Kendall test showed that the area had a significant positive trend in the spring season throughout the province and the summer season in the east of the province. Therefore, the spring season in the area known Extreme Season and June 19, 2009 between the five days of the dust extreme is as an extreme episode with an average AOD of 1.16 and a horizontal visibility of less than two kilometers that it have the highest and most widespread mineral dust. In general, the results of the MACC with multidimensional approach showed that optical depth (AOD, DOD) is a more appropriate criterion than horizontal visibility in determining dust storm.